Didactic poetry as cultural preservation in the anthology Ratapan Laut Sawu by NTT poets - Imelda Oliva Wissang (Universitas Muhammadiyah Malang, 2026)
Poetry as a literary work functions not only as an aesthetic expression, but also as a medium for conveying cultural values ​​and education. However, in academic practice and literary studies, poetry is often understood solely in linguistic terms, leaving its didactic and cultural functions unexplored. This study aims to describe in depth the form, meaning, and function of didactic poetry in preserving cultural heritage, as presented in the anthology